Geophysical characterisation of the groundwater–surface water interface. (November 2017) - McLachlan, P.J.; Chambers, J.E.; Uhlemann, S.S.; Binley, A.
Highlights: Properties and processes of the GW–SW interface are variable in space and time. Revealing hydrological and biogeochemical heterogeneity remains a challenge. Geophysics offer useful tools for addressing variability across multiple scales. Future studies should incorporate geophysical progress gained in parallel fields. Abstract: Interactions between groundwater (GW) and surface water (SW) have important implications for water quantity, water quality, and ecological health. The subsurface region proximal to SW bodies, the GW–SW interface, is crucial as it actively regulates the transfer of nutrients, contaminants, and water between GW systems and SW environments. However, geological, hydrological, and biogeochemical heterogeneity in the GW–SW interface makes it difficult to characterise with direct observations. Over the past two decades geophysics has been increasingly used to characterise spatial and temporal variability throughout the GW–SW interface. Geophysics is a powerful tool in evaluating structural heterogeneity, revealing zones of GW discharge, and monitoring hydrological processes. Geophysics should be used alongside traditional hydrological and biogeochemical methods to provide additional information about the subsurface. Further integration of commonly used geophysical techniques, and adoption of emerging techniques, has the potential to improve understanding of the properties and processes of the GW–SW interface, and ultimately the implications for water quality and environmental health.